2021
DOI: 10.4314/gmj.v55i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reaction reporting by community pharmacists in the Greater Accra Region of Ghana, 2016

Abstract: Objectives: To assess adverse drug reactions (ADRs) reporting and identify factors to improve ADR reporting among community pharmacists in the Greater Accra Region of Ghana.Design: A quantitative cross-sectional study.Setting: Community pharmacies in the Greater Accra Region of Ghana.Participants: We randomly selected 210 pharmacists from a list community of pharmacies in Accra, Ghana. All participants had been practicing in the past one year, with this study being conducted from June to July 2016.Main outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Under-reporting in this Municipality is consistent with previous studies that showed gaps in reporting rates of 79.0% among physicians and 84.0% among Pharmacists in the Greater Accra region [ 13 , 14 ]. We observed a higher gap in reporting rate of 97.2%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Under-reporting in this Municipality is consistent with previous studies that showed gaps in reporting rates of 79.0% among physicians and 84.0% among Pharmacists in the Greater Accra region [ 13 , 14 ]. We observed a higher gap in reporting rate of 97.2%.…”
Section: Discussionsupporting
confidence: 90%
“…In the Greater Accra Region of Ghana, research on under-reporting of ADRs discovered that only 21% of physicians reported ADRs in 2011, although 59.5% had encountered a patient with an ADR [ 13 ]. A similar study among community pharmacists reported that only 16% of those who had seen a patient with a suspected ADR in 2015 reported it [ 14 ].…”
Section: Introductionmentioning
confidence: 99%